Implementation of the Waste Bank Program in Strengthening Religious Character and Environmental Concern of the Community in Kraton Hamlet, Pekalongan City - Naila Rizqiyana; Riza Amelia; Nur Azka Dhiayul Aulia; Muhlisin Muhlisin; Abul Mafaakhir (BALE LITERASI, 2026)
Many urban areas, including Pekalongan City, face significant waste management challenges. The accumulation of household waste is driven by population growth, increased consumption patterns, and a lack of awareness of how to independently sort and process waste, leading to increased environmental pollution. This study, entitled